Forestry Building and Nome Circle, Alaska Yukon Pacific Exposition, Seattle, 1909. - University of Washington Libraries. Manuscripts, Special Collections, University Archives Division (Portland Post Card Co., 1909)
Caption on image: Forestry Building and Band Stand. Official Post Card PH Coll 777.PPCC54 To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number